(untitled) (Samarra Journal of Pure and Applied Science, 2026)
Reactive hyperemia (RH) is a temporary increase in blood flow after ischemia, associated with reduced arterial stiffness and used as a marker of vascular health. Arterial stiffness, a key cardiovascular risk factor, is commonly assessed using pulse transit time (PTT), a non-invasive method. This study examines the effect of occlusion site (arm vs. forearm) on RH magnitude and its relationship with vascular stiffness.Ten healthy males (23.1 ± 5.0 years) participated. PTT and digital pulse amplitude (DPWA) were measured before and after RH induction at baseline and one-minute intervals for five minutes post-induction. Arm occlusion led to a post-occlusion reactive hyperemia index (RHI) increase of 23% at 2 minutes (P < 0.03). Forearm occlusion resulted in RHI increases of 36%, 27%, 27%, and 18% at 2, 3, 4, and 5 minutes, respectively, compared to 1 minute. No significant differences in RHI were found between arm and forearm occlusion, with RH sustained up to 5 minutes after forearm occlusion.PTT increased significantly by 6% and 4% at 1 and 2 minutes after arm occlusion release. Following forearm occlusion, PTT was significantly higher (5%) than baseline only at 1 minute post-release. The peak RHI occurred in the second minute after occlusion release, with forearm RH lasting longer (up to 5 minutes), though magnitudes were similar. Peak PTT, indicating maximum vascular stiffness reduction, occurred in the first minute post-release and may extend into the second minute.